2018
DOI: 10.1029/2018jd028540
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Characteristics of Cloud Radiative Effects on the Greenland Ice Sheet: Discoveries From Multiyear Automatic Weather Station Measurements

Abstract: The impact of clouds on Greenland's surface melt is difficult to quantify due to the limited amount of in situ observations. To better quantify cloud radiative effects (CRE), we utilize 29 automatic weather stations and provide the first analysis on seasonal and hourly timescales in both accumulation and ablation zones. Seasonal CRE shows opposing cycles across geographical regions. CRE generally increases during melt season in the north of Greenland, mainly due to longwave CRE enhancement by cloud fraction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 57 publications
5
45
0
Order By: Relevance
“…Clear‐sky radiation is simulated using the Column Radiation Model (Zender, ) driven by the Level‐3 Atmospheric Infrared Sounder, AIRS (AIRS Science Team/Joao Texeira, ). The uncertainty of clear‐sky simulations is less than 10 W/m 2 (Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clear‐sky radiation is simulated using the Column Radiation Model (Zender, ) driven by the Level‐3 Atmospheric Infrared Sounder, AIRS (AIRS Science Team/Joao Texeira, ). The uncertainty of clear‐sky simulations is less than 10 W/m 2 (Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Clouds warm surfaces through increased longwave radiation (i.e., positive CRE) and cool surfaces through the shortwave shading effect (i.e., negative CRE). The net effect, warming or cooling, strongly depends on location (Wang et al, ). In the high elevation accumulation zone of Greenland, clouds can augment surface heating caused by warm southerly advection, trigger massive surface melt (Bennartz et al, ), and enhance meltwater runoff (Van Tricht et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides temperature and humidity changes, clouds modify the illumination and reflection of the surface. For highly reflecting snow surfaces, radiative transfer simulations show that two processes are crucial: (i) a cloud-induced weighting of the transmitted downward irradiance to smaller wavelengths, causing an increase in shortwave surface albedo, and (ii) a shift from mainly direct to rather diffuse irradiance in cloudy conditions, which decreases the shortwave albedo (Warren, 1982). Observations have shown that there is a tendency for which the surface albedo is larger in cloudy compared to cloud-free conditions (e.g., Grenfell and Perovich, 2008), which was demonstrated for a seasonal cycle by Walsh and Chapman (1998) for highly reflective surface types.…”
Section: Introductionmentioning
confidence: 99%
“…2017; Cullather and Nowicki 2018;Wang et al 2018), and future GrIS melt projections are highly sensitive to modeled cloud properties (Hofer et al 2019). Given the large fluxes of water vapor delivered by ARs, it is likely that some parts of the GrIS experience SMB losses under cloudy conditions during AR events.…”
Section: Introductionmentioning
confidence: 99%